Salidroside Reduces Cell Mobility via NF-κB and MAPK Signaling in LPS-Induced BV2 Microglial Cells. (17th April 2014) - Hu, Haixia; Li, Zuanfang; Zhu, Xiaoqin; Lin, Ruhui; Chen, Lidian
Abstract : The unregulated activation of microglia following stroke results in the production of toxic factors that propagate secondary neuronal injury. Salidroside has been shown to exhibit protective effects against neuronal death induced by different insults. However, the molecular mechanisms responsible for the anti-inflammatory activity of salidroside have not been elucidated clearly in microglia. In the present study, we investigated the molecular mechanism underlying inhibiting LPS-stimulated BV2 microglial cell mobility of salidroside. The protective effect of salidroside was investigated in microglial BV2 cell, subjected to stretch injury. Moreover, transwell migration assay demonstrated that salidroside significantly reduced cell motility. Our results also indicated that salidroside suppressed LPS-induced chemokines production in a dose-dependent manner, without causing cytotoxicity in BV2 microglial cells. Moreover, salidroside suppressed LPS-induced activation of nuclear factor kappa B (NF- κ B) by blocking degradation of I κ B α and phosphorylation of MAPK (p38, JNK, ERK1/2), which resulted in inhibition of chemokine expression. These results suggest that salidroside possesses a potent suppressive effect on cell migration of BV2 microglia and this compound may offer substantial therapeutic potential for treatment of ischemic strokes that are accompanied by microglial activation.